146k views
3 votes
6.4x + 3y=36 when x=3

A. 5
B. 9
C. 6
D. 8

User Matt Self
by
5.8k points

2 Answers

5 votes

Answer:

Step-by-step explanation: First we substitute x as 3

then,the equation will be 4×3+3×y=36(we should no that there is a hidden multiplication sign between 4 and x (3) and 3 and y)

  • also between 4x and 3y there is a hidden multiplication sign

then we can simplify the equations as 12+3y=36

if we want to make the unknown number that is 3y independent we must remove 12.How do we do it? we know that + and - gives neutral so

12-12+3y=36-12(now we have put 12 to the other side making the unknown value independent.Also infront of 12 there is an invisible + sign)

now we can simplify it further +12-12=0

3y=36-12

3y=24

now to find y we have to remove 3 from it .we know its 3×y, right

so if we do the opposite sign 3 will get removed

then 3y ÷3=24÷3 (why i divided 24 also by 3 is , if i add a mathematical equation to one term of the equation i have to do it for others too)

then the equations will be y=8

and the answer is D

User Dbramwell
by
5.7k points
2 votes

Answer:

y = 5.6

Explanation:

6.4x + 3y=36 when x=3

Substituting for x:

6.4*3 + 3y = 36

19.2 + 3y = 36

3y = 36 - 19.2

3y = 16.8

y = 5.6.

User Marsenau
by
6.1k points